Using place branding to attract tourists and residents to Swedish regions - Liljedahl, Joel (2010)
The purpose of this thesis was to investigate how Swedish regions obtain increased growth in tourism and population with the use of place branding. The case studies were conducted with four organizations divided in two Swedish regions: Norrbotten and Jämtland. The organizations in Norrbotten were Swedish Lapland and Regional Development Norrbotten. The organizations in Jämtland were Jämtland Härjedalen Tourism and the county administrative board of Jämtland. The study found that having identified distinct target groups, a well-constructed image and desirable attractions, is crucial when attracting tourists to a region. In order to attract residents, it turned out to be important to create jobs, to use ambassador networks and most importantly, having everyone within a region to strive towards the same goals: something that would be proven rather difficult. Validerat; 20101217 (root)